2007
DOI: 10.1016/j.cell.2007.04.034
|View full text |Cite|
|
Sign up to set email alerts
|

FOXP3 Is an X-Linked Breast Cancer Suppressor Gene and an Important Repressor of the HER-2/ErbB2 Oncogene

Abstract: The X-linked Foxp3 is a member of the forkhead/winged helix transcription factor family. Germline mutations cause lethal autoimmune diseases in males. Serendipitously, we observed that female mice heterozygous for the "scurfin" mutation of the Foxp3 gene (Foxp3(sf/+)) developed cancer at a high rate. The majority of the cancers were mammary carcinomas in which the wild-type Foxp3 allele was inactivated and HER-2/ErbB2 was overexpressed. Foxp3 bound and repressed the HER-2/ErbB2 promoter. Deletion, functionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
463
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(516 citation statements)
references
References 36 publications
27
463
4
Order By: Relevance
“…A nuclear localization of FOXP3 was also reported for most human normal and cancer cells expressing this factor (Zuo et al, 2007b;Ebert et al, 2008;Wang et al, 2009). However, a predominant cytoplasmic FOXP3 labeling was reported for human pancreatic cancer cells (Hinz et al, 2007).…”
Section: Antioncogenic Effect Of Foxp3mentioning
confidence: 73%
See 3 more Smart Citations
“…A nuclear localization of FOXP3 was also reported for most human normal and cancer cells expressing this factor (Zuo et al, 2007b;Ebert et al, 2008;Wang et al, 2009). However, a predominant cytoplasmic FOXP3 labeling was reported for human pancreatic cancer cells (Hinz et al, 2007).…”
Section: Antioncogenic Effect Of Foxp3mentioning
confidence: 73%
“…C-MYC is involved with ras in prostate carcinogenesis (Thompson et al, 1989) and is overexpressed in 80% of the prostate cancer samples. A significant correlation was observed between FOXP3 downregulation and HER-2 and SKP2 or cMYC overexpression in breast and prostate cancer cells (Zuo et al, 2007a(Zuo et al, , 2007bWang et al, 2009).…”
Section: Antioncogenic Effect Of Foxp3mentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the mechanisms determining the role of FOXP3 as negative or positive regulators are still elusive. Interestingly, it has been recently reported that FOXP3 is expressed in mammary epithelial cells and acts as transcriptional repressor of oncogenes [34,35]. This opens new perspectives on the role of FOXP3 in regulating fundamental biological functions of cells, such as cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 99%